Implementation of Wound Hygiene in clinical practice: early use of an antibiofilm strategy promotes positive patient outcomes. (1st January 2022) - Murphy, Chris; Mrozikiewicz-Rakowska, Beata; Kuberka, Izabela; Czupryniak, Leszek; Gómez, Paz Beaskoetxea; Vega de Ceniga, Melina; Walker, Angela; Tomkins, Annabelle; Hurlow, Jenny; Abdo, Raymond; Sandroni, Sara; Marinelli, Elisa
Abstract : Non-healing wounds are devastating for patients, potentially causing long-term morbidity and an impaired quality of life. They also incur a huge health economic burden for health-care services. Understanding of the causes of non-healing wounds has increased significantly. While the need to address the underlying aetiology has always been acknowledged, the role of biofilm in delaying or preventing healing is now accepted. There is a consensus on the need to debride the wound to remove biofilm and then prevent its reformation, to kickstart healing. The potential benefits of incorporating an antibiofilm component within the wound bed preparation framework are clear. However, such a strategy needs to be flexible enough so that it can be implemented by all practitioners, regardless of their expertise or specialty. Wound Hygiene does this. This supplement describes the Wound Hygiene protocol, and includes a selection of case studies on different wound types, demonstrating its ease of use and effectiveness in clinical practice.